1991
DOI: 10.1007/bf01307509
|View full text |Cite
|
Sign up to set email alerts
|

Short-term oral zinc supplementation does not improve chronic hepatic encephalopathy

Abstract: The effect of short-term oral zinc supplementation (zinc sulfate 600 mg/day) on hepatic encephalopathy, was assessed in a double-blind, crossover trial. Fifteen cirrhotic patients with stable, chronic hepatic encephalopathy were randomized to receive either oral zinc or a placebo for 10 days. Following a two-week washout period, these were crossed over to the alternate treatment. Conn's index, which comprises the evaluation of the mental state, asterixis, number connection test, EEG record, and plasma ammonia,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
55
0
3

Year Published

1996
1996
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(60 citation statements)
references
References 17 publications
1
55
0
3
Order By: Relevance
“…Zinc supplementation improves the activity of the urea cycle in experimental models of cirrhosis (28). One trial has evaluated the effects of zinc over a short period (up to a week), without major improvement (29). A positive study administered zinc for 3 months, though the study was not randomized (30).…”
Section: Nutritional Managementmentioning
confidence: 99%
“…Zinc supplementation improves the activity of the urea cycle in experimental models of cirrhosis (28). One trial has evaluated the effects of zinc over a short period (up to a week), without major improvement (29). A positive study administered zinc for 3 months, though the study was not randomized (30).…”
Section: Nutritional Managementmentioning
confidence: 99%
“…The authors found no significant improvement between the 2 groups in a standardized hepatic encephalopathy index. 80 A third nonrandomized, prospective study looked at patients with hepatic encephalopathy treated with oral zinc supplementation. Eight patients with cirrhosis and documented encephalopathy were treated with oral zinc sulfate (600 mg/day) for 3 months and matched for cirrhosis and encephalopathy with 8 control patients.…”
Section: Therapeutic Trialsmentioning
confidence: 99%
“…In a first small study, HE was improved by zinc supplementation Dig Dis 1996;14(suppl 1 ):40-52 [52], However, in two more recent studies oral zinc supplementation (600 mg/day) raised se rum zinc levels significantly and to levels observed in cirrhotics without HE, but no modification in the parameters included in Conn's PSE index were observed [53,54],…”
Section: Other Treatmentsmentioning
confidence: 99%